Robotic cystectomy: surgical technique - Hosseini, Abolfazl; Adding, Christofer; Nilsson, Andreas; Jonsson, Martin N.; Wiklund, N. Peter (BJU international, 2011)
What's known on the subject? and What does the study add? Robotic‐assisted radical cystectomy and pelvic lymphadenectomy have previously been described with an extracorporeal urinary diversion. In this study we describe the technique with totally intracorporeal RARC and orthotopic neobladder. OBJECTIVE • The aim of this report is to describe our surgical technique of robotic assisted radical cystectomy (RARC) with totally intracorporeal urinary diversion in patients with urinary bladder cancer. PATIENTS AND METHODS • A total of 45 patients (7 women and 38 men) with high‐grade and/or muscle‐invasive urothelial cancer of the bladder underwent RARC and intracorporeal urinary diversion at our department. • Orthotopic ileal neobladder was performed in 36 patients and ileal conduit was performed in 9 patients. RESULT • Except in two patients that operation was converted to open surgery during the reconstruction of the orthotopic neobladder, the procedure was performed totally intracorporeal. • The operations time, estimated blood loss and length for hospital stay were decreased over the time. CONCLUSION • RARC with totally intracorporeal urinary diversion is feasible.